Granny Samurai, the Monkey King and I - Chambers, John 1968- (Walker, 2013)
Eccentric young wordsmith Samuel Johnson finds himself home alone while his diplomat uncle is off diverting a crisis in Azerbajan. As Samuel sits penning his memoirs and wondering how to divert the crisis in his own life - namely the big, hairy brute that is Boris Hissocks - he spots the little old lady next door acting very strangely. Is she actually chopping wood with her bare hands? Then the Monkey King comes knocking, and suddenly Samuel's whole world is turned on its head